Health Education Can Improve The Knowledge of Parents About Children's Dental Care. - Alfiani Rohmatulloh (Health Gate, 2026)
Many cases of tooth decay today are caused by a lack of parental knowledge about proper food selection and dental care for their children, especially children aged 4-6 years. This research method uses a descriptive exploratory approach by comparing mothers' knowledge about children's dental care. guardian of "Darma Wanita" Kindergarten 02, Genengan Village. Respondents in this study were 25 parents of students, selected by accidental sampling method. Researchers evaluated respondents' knowledge about children's dental care, with a questionnaire instrument. The results showed a significant increase in parental knowledge from 60% (poor category) to 92% (good category) after the intervention. Supervision in brushing teeth and regular dental check-ups are very important for children.